2000
DOI: 10.1123/ijsnem.10.2.199
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine Supplementation Combined with Aerobic Training Does Not Promote Weight Loss in Moderately Obese Women

Abstract: L-Carnitine (L-C) transports fatty acids into mitochondria for oxidation and is marketed as a weight loss supplement. In a double-blind investigation to test the weight loss efficacy of L-C, 36 moderately overweight premenopausal women were pair matched on Body Mass Index (BMI) and randomly assigned to two groups (N = 18). For 8 weeks the L-C group ingested 2 g twice daily of L-C, while the placebo (P) group ingested the same amount of lactose. All subjects walked for 30 min (60-70% maximum heart rate) 4 days/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 10 publications
5
46
2
6
Order By: Relevance
“…by guest, on May 12, 2018 www.jlr.org Downloaded from liver were increased in aged rats. In the extrahepatic tissues, such as heart, skeletal muscle, and cerebral cortex, carnitine levels in aged rats were significantly decreased compared with those in young rats.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…by guest, on May 12, 2018 www.jlr.org Downloaded from liver were increased in aged rats. In the extrahepatic tissues, such as heart, skeletal muscle, and cerebral cortex, carnitine levels in aged rats were significantly decreased compared with those in young rats.…”
Section: Discussionmentioning
confidence: 90%
“…Brandsch and Eder (51) reported that l-carnitine did not show a positive effect on body weight reduction and body composition among rats fed an energy-deficient diet. Eight weeks of l-carnitine supplementation to moderately overweight premenopausal women did not alter the body weight or fat mass (52). The subjects in these studies were in adult stage and not in senescent stage, so they would have sufficient capacities for carnitine synthesis and transport to ensure competent fatty acid oxidation and lipid metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…(19), com o objetivo de avaliar o aumento da oxidação de ácidos graxos em repouso, tenha encontrado resultados positivos com doses semelhantes à do presente estudo (aproximadamente 2 gramas/dia), outros, utilizando infusão intravenosa de carnitina (3 g) (17), doses inferiores e semelhantes (20)(21)(22), ou doses superiores (4 a 6 g/dia), não confirmaram tais achados (23)(24).…”
Section: Discussionunclassified
“…(24), seria a presença de concentrações normais musculares de carnitina nos indivíduos participantes. Em ambos os estudos, foram excluídos indivíduos vegetarianos, pois se sabe que a carnitina, além de seus precursores lisina e metionina, está presente em maiores quantidades nos alimentos de origem animal.…”
Section: Discussionunclassified
“…Também não foram relacionadas às diferenças metabólicas e bioquímicas (gasto de energia em repouso, QR e ácidos graxos livres) entre os momentos antes e após a suplementação (COELHO et al 2005;COELHO, et al 2010). Da mesma forma, não foram observadas alterações significativas no peso e composição corporal de mulheres na pré-menopausa (19 a 48 anos) com excesso de gordura corporal (média de 35,2%), com a suplementação de L-carnitinia (4g/dia) e realização de exercícios físicos de intensidade moderada, durante um período de 8 semanas (VILLANI, et al 2000).…”
Section: (Figura 2)unclassified